Pencegahan Deforestasi Guna Pemenuhan Hak Atas Lingkungan yang Baik dan Sehat bagi Masyarakat Hukum Adat (Studi Pengesahan European Union Deforestation Regulation) - Aprillia Wahyuningsih (Fakultas Hukum Universitas Islam Indonesia, 2024)
The importance of involving indigenous peoples in preventing deforestation has to be realized. This is not only based on the existence of indigenous peoples, but the state must consider the ability of indigenous peoples to manage forests with their local wisdom. This is also supported by the ratification of the European Union Deforestation Regulation which contains the involvement of indigenous peoples. This paper analyzes the importance of involving indigenous peoples in forest management and its legal adjustment. This research is normative juridical legal research, which examines the legal norms of legislation about its problems in society. Secondary data collection is carried out by literature study through various laws and regulations and literature related to the prevention of deforestation associated with protecting the right to a good and healthy environment for indigenous peoples. This study found that the involvement and protection of indigenous peoples is the fulfilling of the Right to a Good and Healthy Environment. The concept of fulfilling Indonesia's policy adjustments is anchored by the application of the principle of Inalienability to customary land, and the ratification of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) in Indonesian legislation.